Evaluation of AISI H13 and Cr3C2 25NiCr HVOF coatings against die soldering for aluminum high pressure die casting - Mayer, André Renan (2022)
This thesis aims to study high-velocity oxygen fuel (HVOF) coatings for high pressure die casting (HPDC). Wear is found in most fabrication processes and is usually hard to overcome, which is no different for HPDC. Several wear mechanisms are found, and the die is worn as the process occurs. Processes like nitriding and physical vapor deposition are used to improve the surface quality. Nonetheless, these processes only create a superficial change, and the geometry barely changes. Therefore, it is not unusual to recover these surfaces via welding. However, the surface quality achieved via welding is as good as the original. Furthermore, the study of coatings applied via thermal sprays is lacking in the literature. As thermally sprayed coatings have a wide range of properties, a handful of surface engineering problems can be solved by this technique. Coatings based on Cr3C2 25NiCr and AISI H13 were chosen due to the shortage of studies regarding their use for HPDC. Bulk AISI H13 and AISI H13 coated with AlCrN PVD were used as a comparative. Hot corrosion tests were performed to establish coatings performance against molten A383 aluminum alloy. Additionally, a soldering testing process was proposed. Soldering analyses have shown an extensive amount of information regarding the soldering mechanisms and corrosion of the surface. The mechanisms of each surface for soldering and corrosion were evaluated using scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS). Concerning the properties of the surfaces, in general, AlCrN PVD coating showed the best performance. Even so, the change in nitrogen concentration indicates the coating degradation by nitrogen diffusion. The corrosion rate for AISI H13 was diminished when sprayed by HVOF. It was explained by the chemical corrosion during the spraying process, creating iron oxides. However, the uneven corrosion created spikes which increased the surface soldering. The corrosion of Cr3C2 25NiCr was also evaluated and showed a small diffusional layer. However, the soldering forces were high. The stabilization of a Cr-Al-Si strong phase with small spikes created a high adhered intermetallic.